Nuclear inverse polarity papillary lesions lacking myoepithelial cells: A report of two cases. Issue 1 (10th November 2017) - Tajima, Shinya; Maeda, Ichiro; Aida, Yoshio; Kazama, Akio; Koizumi, Hirotaka; Doi, Masatomo; Endo, Akira; Chosokabe, Motohiro; Kishimoto, Keiko; Ono, Takafumi; Tsugawa, Koichiro; Takagi, Masayuki
Abstract : Here, cases of a 68‐ (Case 1) and a 44‐year‐old (Case 2) female are presented. They had an abnormality in the breast, and came to our hospital for further examination and treatment. Radiologically, malignancy could not completely excluded so breast excision was performed. Histologically, both cases revealed papillary neoplastic lesions lined by fibrovascular core and nuclear inverse polarity without atypia. Loss of myoepithelial cells was observed by HE, p63, and calponin. Previous report indicate CK5/6, ER, p63 and MUC3 are important for distinguishing between papillary lesions according to the differential index (based on Allred score) of ([ER total score] + [MUC3 total score])/([CK5/6 total score] + [p63 total score] + 1). Based on this analysis, our two cases had benign lesions. However, based on immunopositivity for cell‐cycle marker Cyclin‐D1, Case 1 was negative, and Case 2 was about 70% positive. Additionally, the Ki‐67 index was <1% in both cases, and no evidence of disease was observed after a maximum 62 months of follow‐up in both cases, despite lack of additional treatment. Thus, we propose that lack of myoepithelial cells in papillary lesions do not necessarily indicate malignancy and are thought to be, at the most, uncertain malignant potential.